Hindbrain Ghrelin Receptor Signaling Is Sufficient to Maintain Fasting Glucose - Scott, Michael M. (Public Library of Science, 2012)
The neuronal coordination of metabolic homeostasis requires the integration of hormonal signals with multiple interrelated central neuronal circuits to produce appropriate levels of food intake, energy expenditure and fuel availability. Ghrelin, a peripherally produced peptide hormone, circulates at high concentrations during nutrient scarcity. Ghrelin promotes food intake, an action lost in ghrelin receptor null mice and also helps maintain fasting blood glucose levels, ensuring an adequate supply of nutrients to the central nervous system. To better understand mechanisms of ghrelin action, we have examined the roles of ghrelin receptor (GHSR) expression in the mouse hindbrain. Notably, selective hindbrain ghrelin receptor expression was not sufficient to restore ghrelin-stimulated food intake. In contrast, the lowered fasting blood glucose levels observed in ghrelin receptor-deficient mice were returned to wild-type levels by selective re-expression of the ghrelin receptor in the hindbrain. Our results demonstrate the distributed nature of the neurons mediating ghrelin action.